Mechanical properties and durability of asphalt-concrete composites enhanced with recycled concrete and porcelain aggregates - Waleed A. Hamad; Ganjeena J. Khoshnaw (MethodsX)
The performance of asphalt–concrete composites in engineering projects is influenced by various factors. Researchers have explored modifying these properties by incorporating recycled materials, often using recycled concrete aggregates in asphalt mixtures with acceptable results. This study investigates whether replacing recycled concrete aggregates with waste porcelain in different amounts could make the concrete stronger, last longer, and improve the environment. • The methodology involved evaluating optimized aggregate proportions through wheel tracking and Böhme abrasion tests while ensuring compliance with Marshall's stability requirements. • This changed mix had a 6 % higher bulk specific gravity (2.24), a better Marshall flow (from 3.5 to 4.6 mm), and a 5 % higher stability (peaking at 33 kN). • The 25 % porcelain replacement exhibited the highest abrasion resistance and extended service life, though it also increased susceptibility to temperature variations.The results show that adding porcelain waste to asphalt mixtures can help make pavement solutions that are durable, cost-effective, and good for the environment. This research supports sustainable infrastructure development by demonstrating an innovative approach to waste utilization in road construction while maintaining high mechanical performance standards.